Quality Of Lenjer Empek-Empek Using Different Brand of Tapioca Flour - Pujayatini, Sri; Elida, Elida; Yuliana, Yuliana; Mustika, Sari (Universitas Negeri Padang, 2024)
This research was motivated by the discovery of various brands of tapioca flour used in making empek-empek lenjer so that the quality produced would be different. This research aims to describe the influence of ingredients in making empek-empek, how to make empek-empek and the quality of empek-empek with different brands of flour which includes materials, tools, processing techniques and quality in terms of shape, color, aroma, texture and taste. thus producing empek-empek-empek with good quality. This type of research is pure experimental research using the R.A.L method including three variables X1 Liaw Toeji Kang brand tapioca, X2. Pak Tani Gunung brand tapioca, X3tapioca Gunung Agung brand were tested on 3 expert panelists, with organoleptic tests, data processing techniques using the ANOVA test followed by the DUNCAN test. The results of the research showed that there was an influence on the quality of empek-empek lenjer on shape (neat), color (before frying), texture (cheeky). So it shows that there is a difference. Meanwhile, there was no influence on the quality of empek-empek lenjer on shape (cylindrical, uniform), color (after frying), aroma (fragrant mackerel and fragrant garlic), texture (dense), taste (savory mackerel fish and savory garlic).